2017
DOI: 10.1021/acs.jcim.6b00426
|View full text |Cite
|
Sign up to set email alerts
|

Creating the New from the Old: Combinatorial Libraries Generation with Machine-Learning-Based Compound Structure Optimization

Abstract: The growing computational abilities of various tools that are applied in the broadly understood field of computer-aided drug design have led to the extreme popularity of virtual screening in the search for new biologically active compounds. Most often, the source of such molecules consists of commercially available compound databases, but they can also be searched for within the libraries of structures generated in silico from existing ligands. Various computational combinatorial approaches are based solely on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 93 publications
(108 reference statements)
0
12
0
1
Order By: Relevance
“…The design of target chemical libraries is actually an undertaking of increasing interest, as illustrated by a number of recent studies that have reported the implementation of artificial intelligence-based algorithms [ 63 , 64 , 65 , 183 , 184 , 185 , 186 ]. One of them is the development of ReLeaSE (Reinforcement Learning for Structural Evolution), which integrates a generative deep neural network with a predictive one into a joint framework for the design of novel compounds satisfying certain chemical requirements, as illustrated with the biased selection of compounds fulfilling a specific range of physical properties (i.e., melting temperature and lipophilicity) or inhibitory activity against the desired target protein (Janus protein kinase 2) [ 62 ].…”
Section: Exploiting Chemical Libraries and Biological Datamentioning
confidence: 99%
“…The design of target chemical libraries is actually an undertaking of increasing interest, as illustrated by a number of recent studies that have reported the implementation of artificial intelligence-based algorithms [ 63 , 64 , 65 , 183 , 184 , 185 , 186 ]. One of them is the development of ReLeaSE (Reinforcement Learning for Structural Evolution), which integrates a generative deep neural network with a predictive one into a joint framework for the design of novel compounds satisfying certain chemical requirements, as illustrated with the biased selection of compounds fulfilling a specific range of physical properties (i.e., melting temperature and lipophilicity) or inhibitory activity against the desired target protein (Janus protein kinase 2) [ 62 ].…”
Section: Exploiting Chemical Libraries and Biological Datamentioning
confidence: 99%
“…Most computer-aided methods for molecular design build a molecule by a combination of predefined fragments (e.g. [ 6 ]). Recently, Ikebata et al [ 7 ] succeeded de novo molecular design using an engineered language model of SMILES representation of molecules [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is required because if the enumeration of molecules was pursued, the libraries for certain applications would become too large for even searching and hence also for the prediction of properties. New generative models could be used to generate focused, smaller virtual libraries that have shifted property distributions tailored for targets 200,203 (Fig. 3).…”
Section: Virtual Screeningmentioning
confidence: 99%